Late diagnosis of breast cancer in a hospital setting in Ouagadougou in 2024: patient characteristics and associated factors - Tognon, Akossito Hermine; Kabore, Ahmed; Yameogo, Aristide; Zongo, Nayi; Bationo, Nestor; Tognon Tchegnonsi, Francis; Walmde, Carine Bagre Sidpa; Djossou, Sègnon Eurydice Elvire; Tokpanoude, Coovi Nonwanou Ignace; Abdoul Halim, Bague; Drabo, Maxime K. (International Journal Of Community Medicine And Public Health, 2025)
Background: Breast cancer, like many other noncommunicable diseases, remains a public health problem today. Although the disease is more common in people over 50, younger women are also affected. The chances of following this disease depend on the stage at which it is diagnosed, since the earlier the diagnosis, the greater the chances of survival. The aim of this study was to determine the factors associated with late diagnosis of breast cancer among women in hospital settings in Ouagadougou (Burkina Faso) in 2024. Methods: This was a cross-sectional analytical study that took place over a period of six months, from February 2 to July 31, 2024, in university hospitals in the city of Ouagadougou. The study included women with confirmed breast cancer. Data were analyzed using Statistical Package for Social Sciences (SSP) software. Results: The study involved 226 women. Among them, the 40-49 age group was the most represented at 39.3%. In addition, 33.63% had a secondary education. More than half (79.65%) lived in urban areas. The frequency of late diagnosis was 32.74% [IC95% (0.674-0.914)]. The factors associated with late diagnosis of breast cancer were the environment in which the patient lived (OR=0.08; p=0.001), The first resort, including traditional medicine (OR=106; p<0.001) and insufficient symptom awareness (OR=4.63; p=0.001). Conclusions: These results reflect a constructive dialogue between traditional and modern medicine, enabling traditional practitioners to be trained to recognize the early signs of breast cancer and to refer patients rapidly to the appropriate health centers for treatment.